2010
DOI: 10.1111/j.1740-0929.2010.00795.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐allergic effects of Lactobacillus crispatus KT‐11 strain on ovalbumin‐sensitized BALB/c mice

Abstract: In t his st udy, we invest igat ed t he effect s of oral ingest ion of Lactobacillus crispatus KT-11 stra in (KT-11) on t he immune response in an allergic rhinit is mouse model, ovalbumin (OVA)-sensit ized BALB/c. Sneezing act ivit y in mice that were administ ered a KT-11-supplement ed diet was significant ly lower than t hat in mice administ ered a KT-11-free diet (cont rol diet) at age of 11 weeks. We found t hat serum OVA-specific immunoglobulin E levels and tot al number of int er leukin (IL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
(7 reference statements)
2
20
0
Order By: Relevance
“…Lactobacillus crispatus is an obligately homofermentative, catalase-negative, Gram-positive bacterium [1]. Numerous studies have shown the considerable probiotic potential of L. crispatus, such as modulating the host's immune system [2], reducing allergic symptoms in mice [3], down-regulating the expression of cancer genes, and inhibiting the proliferation of MDA-MB-231 breast cancer cell lines [4]. In addition, as one of the most detected Lactobacillus species in the healthy female vagina [5], L. crispatus can inhibit vaginal pathogenic microorganisms, and maintain the health of the female reproductive system [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacillus crispatus is an obligately homofermentative, catalase-negative, Gram-positive bacterium [1]. Numerous studies have shown the considerable probiotic potential of L. crispatus, such as modulating the host's immune system [2], reducing allergic symptoms in mice [3], down-regulating the expression of cancer genes, and inhibiting the proliferation of MDA-MB-231 breast cancer cell lines [4]. In addition, as one of the most detected Lactobacillus species in the healthy female vagina [5], L. crispatus can inhibit vaginal pathogenic microorganisms, and maintain the health of the female reproductive system [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous paper, we found that Lactobacillus crispatus KT-11 (KT-11) reduced some allergic symptoms via a decrease in antigen-specific IgE levels in NC/Nga mice, and the reduction was concluded to be due to an adjustment in the Th1/Th2 balance via Tolllike receptor (TLR) 2, nucleotide-binding oligomerization domain (NOD) 1, and/or NOD2 ( 6 ). Moreover, we observed that KT-11 suppressed the acquired allergic responses via not only the adjustment in Th1/Th2 balance but also the decrease in spleen mast cell numbers and antigen-presenting cell numbers in ovalbuminimmunized BALB/c mice ( 7 ). However, the effect of KT-11 on immune systems of normal mice is not known.…”
mentioning
confidence: 67%
“…The proportion of several bacterial genera ( Lactobacillus , Alistipes , Roseburia , Adlercreutzia and Clostridium ) known to have immunomodulatory properties was significantly different between farm and AF mice. Immunomodulatory properties have in particular been shown for Lactobacillus Crisptatus , and for Clostridia colonization in relation to IL‐22 up‐regulation in lamina propria lymphocytes . In contrast to AF mice whose microbiome had higher diversity at 4 weeks than at 20 weeks of age ( P = 0.0079), the Shannon diversity index of farm mice significantly ( P = 0.032) increased during this time interval from 2.89 (range 1.8–3.18) to 3.97 (range 3.84–4.16).…”
Section: Discussionmentioning
confidence: 99%